(untitled) (Revista Argentina de Cirugía, 2014)
Background: bariatric surgery has been established as a standard practice for long-term treatment of morbid obesity and its complications. Objectives: to describe the morbidity and mortality of our series of patients undergoing laparoscopic roux-en-ygastric bypass (lrygbp) and laparoscopic sleeve gastrectomy (lsg). Place of application: private hospitals. Design: retrospective, descriptive study of prospectively collected data. Population: patients who underwent lrygbp or lsg. Assessment measures: variables of morbidity and mortality. Method: analysis of database. Results: between january 2008 and february 2012, 1020 patients underwent bariatric surgery. All of the patients included in the study had at least 3 months follow-up. Demographics: mean age, 42 ±11; height, 1.7 ±0.1 m; initial weight, 131 ±27 kg; initial bmi, 47 ±8 kg/m2. Type of surgery: lrygbp 79% and 21% lvg. Complications: anastomotic dehiscence, 1 (0.1%); gastrointestinal bleeding, 8 (0.8%); intraabdominal bleeding, 9 (1%); internal hernias, 5 (0.5 %), stenosis, 44 (5%). No pulmonary embolism was observed. Operative time was 150 ±21 minutes; average hospital stay was 48 ±56 hours and mortality rate was zero. The percentage of excess weight loss (% ewl) at 6, 12, 18 and 24 months were 66 ±15, 76 ±18, 75 ±22, and 73 ±24, respectively. Conclusions: in our series of 1020 patients, the morbidity associated with bariatric surgery was very low and the mortality was nil. Also, the results in terms of weight loss were favorable, suggesting that laparoscopic roux-en-y gastric bypass and laparoscopic sleeve gastrectomy are both safe and effective for the surgical treatment of obesity.